The Association Between Depressive Symptoms, Anger, and Perceived Support Resources Among Underserved Older HIV Positive Black/African American Adults - Whitehead, Nicole Ennis (Mary Ann Liebert, Inc., 2014)
By 2015, half of those living with HIV in the United States will be≥50 years of age. Research suggests that perceived social support is an important factor in maintaining positive health behaviors in this population. The present study examined the relationship between depressive symptoms and trait anger on perceived social support in a sample of low-income HIV positive (HIV+) African Americans≥50 years of age. Additionally, we examined life stressors moderated the relationship between mental health and perceived support. This study includes 95 HIV+ men and women≥50 years of age who identify as black/African American. As expected, depressive symptoms and trait anger showed a strong inverse relationship with perceived support resources. Furthermore, life stressors also showed a strong inverse relationship with perceived support. However, life stressors did not moderate the relationship between depressive symptoms and anger. Instead life stressors demonstrated a strong independent relationship with perceived support. The association between depressive symptoms, trait anger, life stressors, and lower perceived support suggests that these factors play a role in one's ability to access needed support resources. Greater perceived support is associated with improved health in HIV+ persons, and may be especially important in tailoring interventions for those≥50 years of age.